Clinical and Demographic Profile of Chronic Kidney Disease Patients Undergoing Kidney Transplantation at a Tertiary Hospital in Indonesia - Khairil Faiz Amir; Ade Asyari; Harun, Harnavi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Chronic kidney disease (CKD) is a global health problem, and kidney transplantation is the treatment of choice for end-stage renal disease (ESRD). This study aimed to describe the clinical and demographic profile of CKD patients undergoing kidney transplantation at Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: A descriptive retrospective study was conducted using medical records of CKD patients who underwent kidney transplantation between 2015 and 2023. Data on age, gender, duration of hemodialysis, donor-recipient relationship, blood pressure, blood type, crossmatch results, serum urea and creatinine levels, and etiology of CKD were collected and analyzed. Results: The study included 18 patients, all aged 19 to 59 years. The majority of patients were male (55.6%) and had undergone hemodialysis for less than 3 years (55.6%). Prehypertension and hypertension were the most prevalent blood pressure categories (44.4% each). Blood types A and O were most common (27.8% each), with consistent crossmatch results across groups. High levels of serum urea and creatinine were predominant, and hypertension was the most frequent etiology of CKD (66.7%). Conclusion: This study provides valuable insights into the characteristics of CKD patients undergoing kidney transplantation in Indonesia. The findings highlight the importance of early detection and management of CKD, particularly hypertension, to reduce the burden of ESRD and the need for transplantation.